2020
DOI: 10.1101/2020.09.01.278697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BonA fromAcinetobacter baumanniiforms a divisome-localized decamer that supports outer envelope function

Abstract: Acinetobacter baumannii is a high-risk pathogen due to the rapid global spread of multi-drug resistant lineages. Its phylogenetic divergence from other ESKAPE pathogens means that determinants of its antimicrobial resistance can be difficult to extrapolate from other widely studied bacteria. A recent study showed that A. baumannii upregulates production of an outer-membrane lipoprotein, which we designate BonA, in response to challenge with polymyxins. Here we show that BonA has limited sequence similarity and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Interestingly, when during the post‐CASP analysis we repeated the docking experiment using the same monomer model, but without the N‐terminal helix, the docking was highly successful [Figure 7(C)]. Of note, in solution this protein exists as a mixture of a monomer and a decamer, and the dimer observed in the crystal might represent an intermediate state in decamerization 43 …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, when during the post‐CASP analysis we repeated the docking experiment using the same monomer model, but without the N‐terminal helix, the docking was highly successful [Figure 7(C)]. Of note, in solution this protein exists as a mixture of a monomer and a decamer, and the dimer observed in the crystal might represent an intermediate state in decamerization 43 …”
Section: Resultsmentioning
confidence: 99%
“…BonA is tethered to the membrane by an N‐terminal cysteine‐linked acyl chain, which is connected to the first BON domain by a 27 amino acid linker. BonA forms a decamer, composed of a pentamer of dimers, with the 27 amino acid N‐terminal linker playing an important but undefined role in decamer formation 73 …”
Section: Resultsmentioning
confidence: 99%
“…However, protein structural information can provide insight into cryptic actives sites, not easily discernible from analysis of amino acid sequence alone. Additionally, the initial purification and analysis of BonA showed that it forms a decamer 73 . Other BON domain‐containing proteins had not previously been shown to oligomerize, so it was unclear how the decamer of BonA formed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the structure and the oligomeric state of this protein are dynamic. It exists as a monomer, a dimer or a decamer in solution, and the dimer observed in the crystal might represent an intermediate state in decamerization 42 .…”
Section: Free Dockingmentioning
confidence: 99%